Deiksis Waktu dalam Pertunjukan Wayang Kulit Purwa Gagrag Banyumasan Lakon Bawor dadi Ratu oleh Dalang Ki Sugino Siswacarita - Astiana Ajeng Rahadini (Jurnal Penelitian Pendidikan, 2016)
This research provided the account of describing the kinds of deixis time found in thepuppet show purwa gagrag Banyumasan: Bawor dadi Ratu by puppeteer Ki SuginoSiswacarita. The source of the research data was the VCD recording of a puppet showpurwa gagrag Banyumas: Bawor dadi Ratu by puppeteer Ki Sugino Siswacarita. Thefocus of the research was the kinds of time deixis found in the puppet show. Then, thedata collection techniques were by listening, tapping, and noting. The analysis of thedata was classifying and analysing the data based on the kinds of time deixis. To get thetrustworthiness of the data, the triangulation of source was fulfilled. The dependabilityof the data was obtained through repeatedly rotating and listening to the utterancesin a puppet show. The findings revealed that the found time deixis was in the form ofwords (monomorphemic and polymorphemic) and phrases (attributive and appositiveendocentric, as well as exocentric). Finally, the time deixis found in a puppet show purwagagrag Banyumasan: Bawor dadi Ratu by puppeteer Ki Sugino Siswacarita, were (1) thepast time deixis, (2) the present time deixis, and (3) the future time deixis.